Application of arc emission spectrometry and portable X-ray fluorescence spectrometry to rapid risk assessment of heavy metals in agricultural soils. (June 2019) - Wan, Mengxue; Hu, Wenyou; Qu, Mingkai; Tian, Kang; Zhang, Haidong; Wang, Yan; Huang, Biao
Highlights: PXRF and AES were used together to rapidly measure major heavy metals in agricultural soils. The rapid analysis showed accuracy comparable to that of conventional analysis. Both rapid and conventional methods produced similar heavy metal classification and spatial patterns. The rapid methods provided economic risk assessment of agricultural soils. Abstract: Ecological risk assessment of soil is commonly performed by determining heavy metals (HMs) through conventional laboratory analysis, which is cost-, time- and labor-consuming, especially in large-scale agricultural soils. Therefore, appropriate cheaper and faster analytical methods of comparable accuracy are urgently required. In this study, rapid analyses of HMs were performed via Portable X-ray fluorescence (PXRF) spectrometry and arc emission spectrometry (AES) in agricultural soils from a representative greenhouse vegetable area on the east bank of Dianchi Lake in Kunming City, Yunnan Province, southwest of China. Here AES was specifically used as a replacement of PXRF for measuring Cd in soil because the measurement limit of PXRF for Cd is usually higher than the normal content of Cd in agricultural soils. The performances of rapid analysis and conventional laboratory analysis were compared and evaluated, and ecological risk was assessed with the Nemerow composite pollution index for classifying HM contamination grades and Kriging interpolation for mapping spatial variation. Results showed that the PXRF and AES were applicable and accurate with the relative standard deviation (RSD) and the relative percent difference (RPD) for HMs being within 20%. Significant positive correlations were found between the rapid analysis results and conventional laboratory analysis results for both certified reference materials and collected soil samples. The classification of soil HM contamination grades and their spatial patterns were similar between the rapid analysis and laboratory analysis. Overall, results of the rapid analysis were almost identical to those of conventional laboratory analysis. Therefore, rapid HM analysis using PXRF and AES is effective and economic for accurately assessing ecological risk of agricultural soils in greenhouses.